2021
DOI: 10.1007/s10803-021-05075-9
|View full text |Cite
|
Sign up to set email alerts
|

Expressed Emotion in Families of Children With and Without Autism Spectrum Disorder, Cerebral Palsy and Down Syndrome: Relations with Parenting Stress and Parenting Behaviors

Abstract: The research includes a subset of data on parenting behavior and child behavior, which has been previously published (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 74 publications
1
32
0
Order By: Relevance
“…Educational level, number of children, and average monthly income were the only significant variables that were associated with the scores of the environmental domain of the QoL. The socioeconomic status and educational levels of the parents were also previously reported to be significantly correlated, and it has been demonstrated that it can significantly impact the association between DS children and their parents [ 8 , [33] , [34] , [35] ].…”
Section: Discussionmentioning
confidence: 95%
“…Educational level, number of children, and average monthly income were the only significant variables that were associated with the scores of the environmental domain of the QoL. The socioeconomic status and educational levels of the parents were also previously reported to be significantly correlated, and it has been demonstrated that it can significantly impact the association between DS children and their parents [ 8 , [33] , [34] , [35] ].…”
Section: Discussionmentioning
confidence: 95%
“…Two of the other family concepts (family appraisal and family adaptation) were assessed in 19 studies. Twelve of the 19 studies that included an assessment of family appraisal were qualitative (Clark et al, 2020; De Clercq, Prinzie, Swerts, et al, 2022; De Clercq, Prinzie, Warreyn, et al, 2022; Duarte et al, 2022; Finkelstein et al, 2021; Huiracocha et al, 2017; Korkow-Moradi et al, 2017; Persons, 2017; Ronca et al, 2019; Sheldon et al, 2021; Steffensen et al, 2022; Watanabe et al, 2021), six were quantitative (Caples et al, 2018; Choi & Van Riper, 2020; Darla & Bhat, 2021; A. Lee et al, 2020; Van Riper et al, 2018, 2021), and one was mixed-methods (E.…”
Section: Resultsmentioning
confidence: 99%
“…x De Clercq, Prinzie, Warreyn, et al, 2022 This study examined the family emotional climate as assessed by 5-minute speech samples and the relation with parenting stress and parenting behaviors among parents of children (6-17 years, 64.7% boys) with ASD, CP, DS, and without any known disability (n = 447)…”
Section: Respondentsmentioning
confidence: 99%
“…Conversely, stress levels were more influenced by the severity of the symptoms in parents of children with DS or WS than those of children with ASD. A more recent study using a cross-disability approach found that emotion expression (in particular, the expression of high criticism) was differently associated with parenting stress in parents of children with DS compared with parents of children with other forms of disability [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…In sum, it emerges that the proper identification of the specific factors affecting parental stress in DS could be the first necessary step for the setting up of adequate interventions. Parents of children with DS experience significantly lower levels of parenting stress than parents of children with other NDDs do, such as ASD [ 33 , 37 , 38 , 39 , 40 , 41 ], Prader–Willi syndrome [ 42 ], 22q11.2 deletion syndrome [ 39 ] and other forms of ID [ 26 , 43 ]. This phenomenon has been described in terms of a Down Syndrome advantage [ 44 ], according to which families of children with DS experience greater wellbeing than families of children with other kinds of ID.…”
Section: Introductionmentioning
confidence: 99%